Reflejos de un espejo fracturado - Baraona Cockrell, Miguel (Editorial Universidad Nacional (EUNA), 2009)
This book attempts to establish the connection between the changing discourse of the social sciences and the structuring process of various ethnic orders. The evolution of the ethnic theme in the social sciences throughout the 20th century is analyzed.